Hybrid Learning: Analysis of Transformation of Islamic Education in Digital Era - Hadiati, Eti; Dwiyanto, Agus; Setianingrum, Diah Ayu; Amroini, Ari Zulfa (International Journal of Islamic Studies Higher Education, 2023)
The purpose of this research is to present perspectives on education management in hybrid learning during the COVID-19 pandemic transition. The research method used is a literature study method that is collected from a collection of reference data from experts as well as from a total of 47 national journals and five nouveau international journals published in the last 5 years. This method is carried out by carefully reading various data sources that will later be relevant to the topic studied by the author, which is then conveyed in the form of a description with several additional elements. The COVID-19 pandemic has made the education management process undergo various changes and adjustments in many elements, including adjustments to education management from pandemic status to a new normal transition. During this time, teaching is carried out using hybrid and blended learning approaches, which have proven to be beneficial and effective in mitigating the possibility of learning loss as a result of the pandemic's effects. The impact of literature research on education during the COVID-19 pandemic with the implementation of hybrid and blended learning provides valuable insights for the general public, future researchers, and all parties looking for a practical and adaptable educational approach in difficult times. Although this style of learning is the answer and solution in the world of education during the pandemic transition, there are several challenges in the implementation stage.